Relationship between knowledge and attitudes of third trimester pregnant women with iud contraception selection after childbirth - Lina Haryani; Shafa Mufidah (Institute of Computer Science (IOCS), 2022)
IUD Post Partum (PPIUD) is an effective and safe method of contraception that is used up to 48 hours after the procedure. Inappropriate understanding of the IUD Post Partum can have an impact on not achieving the family planning program and in general respondents who have a positive attitude will have good knowledge about IUD Post Partum. The purpose of this study was to determine the description and relationship of the level of knowledge and attitudes of pregnant women in the third trimester with the IUD selection plan after childbirth. The current study used complete sampling with a sample size of 34 adult males and used a study survey analytic technique. This analysis tool makes use of lembar kuesioners. Data analysis includes both univariate and bivariate analyses (uji chi square). The study was conducted from September 2021 to February 2022. The results showed that there was a relationship between the level of knowledge of third trimester pregnant women and the plan for choosing IUD post partum, p value=0,025 (p value <0,05) and there was a relationship between the attitude of third trimester pergnant women and the plan for choosing IUD post partum. P value = 0,001 (p value < 0,05)